Entre jogos e contracondutas: o uso de jogos de simulação como catalisadores de contracondutas sócio-espaciais - Tiago Cicero Alves (2018)
This thesis presents some application of simulation games as part of technical assistence on fragile communities in the Southeast of Brazil. The research began through the contact with a local squatter from Belo Horizonte and the development of the board game Ocupe, which the goal is to increase the residents spatial imaginary. The creation of the game was influenced by the concept of open game proposed by Vilém Flusser and the cybernetic terms structure and organization (which means the games rules and repertoire and how the relation between them happen). The game Ocupe was played in two local squatters (Paulo Freire and Terra Nossa) in turns that helped to raised demands and to mobilize discussions among the residents. From these experiences the most relevant outcome was the reflection and criticism of some decisions that organize the squatter space itself, although in the most part of the game the participants only reproduced the concrete squatter spaciality on the board. The central hypothesis of the thesis is that the notion of counterconduct, as worked by Michel Foucault, is considered as a theoretical horizon during the creation of simulation games mechanics. In this way, thought "and if" exercised during a match can be catalyzed to a possible socio-spatial counterconduct on the part of those who plays. As an example, the game Le Jeu de la Guerre, developed by Guy Debord, is presented, which reveals the current power relations through the recognition of "favorable strategic situations". A reproduction of the game was developed in the laboratory LAGEAR (UFMG) and played with some Architecture and Geography students. The notion of counterconduct fueled the creation of the game Bívio, whose goal is the discussion of cultural assets and heritage and its relationship with the Glauras spaces (a district of Ouro Preto). The conduct of the theme is developed so that the spaces are valued from their manufacture production. Finally, the prototypes that precede the final version are presented, as well some test turns played in as the laboratory and in Glaura.